Ovarian serous carcinoma: recent concepts on its origin and carcinogenesis - Li, Jie (BioMed Central, 2012)
Recent morphologic and molecular genetic studies have led to a paradigm shift in our conceptualization of the carcinogenesis and histogenesis of pelvic (non-uterine) serous carcinomas. It appears that both low-grade and high-grade pelvic serous carcinomas that have traditionally been classified as ovarian in origin, actually originate, at least in a significant subset, from the distal fallopian tube. Clonal expansions of the tubal secretory cell probably give rise to serous carcinomas, and the degree of ciliated conversion is a function of the degree to which the genetic hits deregulate normal differentiation. In this article, the authors review the evidentiary basis for aforementioned paradigm shift, as well as its potential clinical implications.